INDONESIAN SUFI IN MALAY WORLD: A Preliminary Exploration with Reference to Tariqa Naqshbandiyya-Khalidiyya Babussalam (TNKB) (State Islamic University (UIN) of Sunan Ampel Surabaya, 2017)
This article is an initial exploration of Indonesian Sufi, developed in the Malay world of Indonesia and Malaysia. The spread of this particular tariqa (sufi’s order) relates specifically to the mandate received by Tuan Guru of TNKB, as its certified Shaykh, who then actively involved in the network acitivity by visiting the Malay Sultanate areas scattered in the Malay Peninsula. This research reveals the incorporation of some elements of different tariqas in the “form” of TNKB, such as Tariqa Shazaliyya and Tariqa Sammaniyya, as well as adaptation of local culture of Malays ethnic which become part of its unique ritual. Supported by the Sultan, TNKB has become the “official order” of Malay Sultanate, which covers area of Riau, Sumatera Utara (North Sumatera) in Indonesia as well as Johor in Malaysia—with caliph as its “agent”.